DVD-0235 (Hailey & Bailey's silly fight Lighthouse Educational Corp., 2008)
An animated children$1 (Bs film that teaches positive values and conflict resolution through the story of Hailey and Bailey and their humorous disagreement.s
Produced under licensed agreement for distribution in the Philippines by Lighthouse Educational Corp.
General Audience
Keywords: Conflict resolution; Christian life